NIR Photosensitizer for Two-Photon Fluorescent Imaging and Photodynamic Therapy of Tumor - Chen, Lujia; Chen, Meijuan; Zhou, Yuping; Ye, Changsheng; Liu, Ruiyuan (Frontiers in Chemistry, 2021)
Preparation of near-infrared (NIR) emissive fluorophore for imaging-guided photodynamic therapy has attracted enormous attention. Hence, NIR emissive fluorophore of two-photon fluorescence imaging, and photoactive cancer cells apoptosis are highly desirable. In this study, a novel D-pai-A structured NIR photosensitizer (TTRE) is synthesized. TTRE demonstrates near-infrared (NIR) emission, good biocompatibility, and superior photostability, which can act as two-photon fluorescent agent for clear visualization of living cells and vascular in tissues with deep-tissue penetration. The efficacy of TTRE as photosensitizer is exploited in vitro and in vivo. All these results confirm that TTRE can serve as potential platform for two-photon fluorescent imaging of cells/tissues and photodynamic therapy.